2013
DOI: 10.1186/1471-2490-13-35
|View full text |Cite
|
Sign up to set email alerts
|

Successful reduction of hospital-acquired methicillin-resistant Staphylococcus aureus in a urology ward: a 10-year study

Abstract: BackgroundTo eradicate hospital-acquired methicillin-resistant Staphylococcus aureus (MRSA) using a stepwise infection control strategy that includes an avoidance of antimicrobial prophylaxis (AMP) based on surgical wound classification and an improvement in operative procedures in gasless single-port urologic surgery.MethodsThe study was conducted at an 801-bed university hospital. Since 2001, in the urology ward, we have introduced the stepwise infection control strategy. In 2007, surveillance cultures for M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…Aging and diabetes mellitus, which might exacerbate infectious diseases, were also risk factors for prolongation of hospitalization. Regulation and control of infectious diseases during hospitalization has been enforced by the infectious diseases control division in the hospital, ( 13 , 15 , 16 ) and the present study clearly demonstrated the importance of infectious disease control during hospitalization.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Aging and diabetes mellitus, which might exacerbate infectious diseases, were also risk factors for prolongation of hospitalization. Regulation and control of infectious diseases during hospitalization has been enforced by the infectious diseases control division in the hospital, ( 13 , 15 , 16 ) and the present study clearly demonstrated the importance of infectious disease control during hospitalization.…”
Section: Discussionsupporting
confidence: 65%
“…Infectious diseases during hospitalization were caused by several factors including nosocomial infection and infection following intensive intervention including surgery. ( 13 , 14 ) The results of the present study suggest that infectious disease complications during hospitalization were linked to increased severity of the patient’s illness. This was demonstrated by the higher mortality rate in group II (the prolonged hospitalization group) of 1.49%, which was significantly higher than in group I (0.97%).…”
Section: Discussionmentioning
confidence: 49%
“…27 Moreover, it may enable the development of Clostridium difficile colitis 28 and drug-resistant bacteria, 1-3 which usually require further antibiotic therapy, longer hospital stays, and increased hospitalization costs. We have previously reported that hospital-acquired MRSA and clinically significant MRSA infections substantially decreased after the stepwise reduction of AMP in our urology ward, 29 suggesting that reducing the use of AMP may lower MRSA rates.…”
Section: Discussionmentioning
confidence: 86%
“…A multicenter study conducted in China between 2013 and 2015 showed that the MRSA infection was significantly associated with higher total hospital cost, longer length of hospital stay, and increased mortality rate as compared to Methicillin-sensitive Staphylococcus aureus (MSSA) infection, especially in patients with underlying diseases such as malignancy or chronic pulmonary diseases [ 5 ]. However, evidence from high-income countries proved that implementing an effective hospital infection control program significantly reduces the morbidity and mortality of MRSA-associated infections [ 6 , 7 , 8 ]. The improvement in hand hygiene compliance can significantly decrease MRSA rates in hospitals [ 9 ].…”
Section: Introductionmentioning
confidence: 99%